Sự phát triển trí tuệ của trẻ em mẫu giáo 5-6 tuổi - Nguyễn, Thạc (Bộ Giáo dục và Đào tạo, 2013)
The article covers the situation of levels in intellectual development and the psychological comporent parts in intelligence of 5-6 year old children. It also clarifies objective and subjective variables in fluencing the child intellectual influencing the child intellectual development and the suggestions to get children ready for primary school.